Widowhood, solitude and sexuality in old age: confronting and overcoming mechanisms - Verónica Montes de Oca Zavala (Kairós Gerontologia, 2012)
Widowhood is usually associated to negative aspects of life mainly when the people involved are in old age. However, depending on the moment this phase of life is faced, it is possible to activate certain mechanisms allowing confrontation and reorganization of life. This article presents, from an exploratory, qualitative and analytical perspective, three case studies in the state of Mexico showing how widowhood is seen, whatit means in old age, its social and economic impacts, as well as its discourses and antidiscoursesgenerated from the subjects analyzed so as to overcome solitude, isolation, the need for afection and love that go beyond what family and children provide for. Sexuality is seen from a critical perspective and it is an element that stands out both in the narrative of such three cases and when compared to the traditional view that analyses widowhood and old age. This article is composed of a bibliographic review, objectives, methodology and a section of final results and reflections.